2020
DOI: 10.3390/app10134666
|View full text |Cite
|
Sign up to set email alerts
|

Low-Speed Bearing Fault Diagnosis Based on Permutation and Spectral Entropy Measures

Abstract: Despite its influence on wind energy service life, condition-based maintenance is still challenging to perform. For offshore wind farms, which are placed in harsh and remote environments, damage detection is critically important to schedule maintenance tasks and reduce operation and maintenance costs. One critical component to be monitored on a wind turbine is the pitch bearing, which can operate at low speed and high loads. Classical methods and features for general purpose bearings cannot be applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The validity of this EI is proven by Sandoval et al [ 74 ], who showed that the values of spectral entropy of the SepEn for healthy bearings are higher than the values obtained from vibration signals of bearings with damage.…”
Section: Theoretical Background: Classic and Entropy Indicatorsmentioning
confidence: 88%
See 4 more Smart Citations
“…The validity of this EI is proven by Sandoval et al [ 74 ], who showed that the values of spectral entropy of the SepEn for healthy bearings are higher than the values obtained from vibration signals of bearings with damage.…”
Section: Theoretical Background: Classic and Entropy Indicatorsmentioning
confidence: 88%
“…Whereas open data sets are available for regular bearings in different repositories [ 71 , 72 , 73 ], low-speed bearing data are scarce and usually proprietary. In this work, to evaluate the proposed strategy, a dataset of vibration signals from low-speed bearings was obtained via an experimental test rig using thrust ball bearings [ 74 ] ( Figure 2 a). Thus, the specific bearing operating conditions were established according to the literature [ 22 , 75 , 76 ]: (i) The bearings rotated at a very low speed (between 5 and 10 rpm), and (ii) the test rig applied a high force (50 kN) to the bearing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations